Peer‐pressure and overuse: The effect of a multimodal approach on variation in benzodiazepine prescriptions in a network of public hospitals - Del Giorno, Rosaria (Int J Clin Pract, 2019)
BACKGROUND: The epidemic phenomenon leading to a progressive increase in benzodiazepine prescriptions represents a challenge for healthcare systems. In the hospital setting, indicators of prescription variation and potential of overuse are lacking and are rarely monitored. Inter‐hospital monitoring/benchmarking, via peer‐pressure, can foster the motivation to change. The aim of this investigation was to analyse whether, the reduction in new benzodiazepine prescriptions obtained thanks to a Choosing Wisely campaign, also contributed to reducing inter‐hospital variation. METHODS: Secondary analysis of a multicentre longitudinal intervention in a network of five teaching hospitals in Switzerland. We set out to explore the effect, on inter‐hospital benzodiazepine prescription variation, of a continuous monitoring/benchmarking strategy, which was proven effective in reducing the intra‐hospital prescription rate. The variance was used to assess inter‐hospital variation. To investigate the impact of the intervention a segmented regression analysis of interrupted time series was performed. RESULTS: A total of 36 299 admissions over 42 months were analysed (1 July 2014 to 31 December 2017). Before the intervention a significant constant upward trend in inter‐hospital variability was found (+0.901; SE 0.441; P < .05). After the intervention, the variance trend line significantly changed, decreasing by −0.257 (SE 0.005: P < .001) and producing by December 2017, a 27% absolute reduction. CONCLUSIONS: Thanks to a multimodal approach based on monitoring‐benchmarking, a significant reduction in inter‐hospital benzodiazepine prescription variation was obtained. Aligning to peer strategy is a spontaneous consequence of open benchmarking that can be used to convert a variation‐based suspicion of overuse, into an occasion to actively review prescription habits.